4(6+3.2w)+7=60.2

Simple and best practice solution for 4(6+3.2w)+7=60.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(6+3.2w)+7=60.2 equation:


Simplifying
4(6 + 3.2w) + 7 = 60.2
(6 * 4 + 3.2w * 4) + 7 = 60.2
(24 + 12.8w) + 7 = 60.2

Reorder the terms:
24 + 7 + 12.8w = 60.2

Combine like terms: 24 + 7 = 31
31 + 12.8w = 60.2

Solving
31 + 12.8w = 60.2

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-31' to each side of the equation.
31 + -31 + 12.8w = 60.2 + -31

Combine like terms: 31 + -31 = 0
0 + 12.8w = 60.2 + -31
12.8w = 60.2 + -31

Combine like terms: 60.2 + -31 = 29.2
12.8w = 29.2

Divide each side by '12.8'.
w = 2.28125

Simplifying
w = 2.28125

See similar equations:

| 2(1)+1-3(1)+4= | | -12t+12t+-t+-11=3 | | 5(p-8)=-36+5p | | A(n)=2+(4-1)(-2.5) | | X+2x+x=32 | | 2(3x+6)=-36+30 | | h-h+h=7 | | 4t-t=18 | | 8(x-0.25)=4(2x-0.5) | | 5/34*17/20= | | 2q-5q+-9q=12 | | 5x-3=93 | | 0.20x+0.45(30)=25.5 | | 8-(3n-6)=9-4n | | (x-2)(x+1)=3 | | 11-2x=5(x+1)-7x | | t^6+6t^3-27=0 | | 9r+3=37r+7 | | 3(3+c)=2(c-7) | | k-2k+-7k=-18 | | 5x+21+3x=29 | | 10-2r=28 | | 3(n+1)-(7n-5)=-5n | | 2.33=(x-78)/3 | | 4+8=6+g | | a-18=7a | | 2(0)+0-3(0)+4= | | 0.11p+1.25y=8.62 | | 15t+-13t+-15=-19 | | 10v=-6 | | 4(x+9)=7+3x | | 2x-1+-2x^2=0 |

Equations solver categories